Overview of Ivabradine Drug: Use and History - Melviana Lubis (Universitas Muhammadiyah Sumatera Utara, 2023)
Despite the significant advances in management and prevention, heart failure still cause high mortality and morbidity. Ivabradine is one example of a new drug used in the treatment of heart failure with decreased ejection fraction. Ivabradine history and use is interesting that it can improve our understanding to cardiovascular pathophysiology. There may also be extended indications for Ivabradine use in the future.